Structural Dynamics of the Functional Nonameric Type III Translocase Export Gate. Issue 21 (15th October 2021) - Yuan, Biao; Portaliou, Athina G.; Parakra, Rinky; Smit, Jochem H.; Wald, Jiri; Li, Yichen; Srinivasu, Bindu; Loos, Maria S.; Dhupar, Harveer Singh; Fahrenkamp, Dirk; Kalodimos, Charalampos G.; Duong van Hoa, Franck; et al.
Graphical abstract: Highlights: Intrinsic dynamics of the type III protein translocase export gate SctV are unknown. Self-nonamerized SctV ring is a high affinity chaperone/secreted client receptor. HDX-MS revealed intrinsic dynamics that allow rigid body "pinching" domain motions. The ring periphery is a wide, multivalent chaperone trap essential for secretion. Intrinsic dynamics likely underlie chaperone/client promiscuity and ring allostery. Abstract: Type III protein secretion is widespread in Gram-negative pathogens. It comprises the injectisome with a surface-exposed needle and an inner membrane translocase. The translocase contains the SctRSTU export channel enveloped by the export gate subunit SctV that binds chaperone/exported clients and forms a putative ante-chamber. We probed the assembly, function, structure and dynamics of SctV from enteropathogenic E. coli (EPEC). In both EPEC and E. coli lab strains, SctV forms peripheral oligomeric clusters that are detergent-extracted as homo-nonamers. Membrane-embedded SctV9 is necessary and sufficient to act as a receptor for different chaperone/exported protein pairs with distinct C-domain binding sites that are essential for secretion. Negative staining electron microscopy revealed that peptidisc-reconstituted His-SctV9 forms a tripartite particle of ∼22 nm with a N-terminal domain connected by a short linker to a C-domain ring structure with a ∼5 nm-wide inner opening. The isolated C-domain ring was resolved with cryo-EM at 3.1 Å and structurally compared to other SctV homologues. Its four sub-domains undergo a three-stage "pinching" motion. Hydrogen-deuterium exchange mass spectrometry revealed this to involve dynamic and rigid hinges and a hyper-flexible sub-domain that flips out of the ring periphery and binds chaperones on and between adjacent protomers. These motions are coincident with local conformational changes at the pore surface and ring entry mouth that may also be modulated by the ATPase inner stalk. We propose that the intrinsic dynamics of the SctV protomer are modulated by chaperones and the ATPase and could affect allosterically the other subunits of the nonameric ring during secretion.